2008
DOI: 10.1152/ajpheart.00160.2007
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of X-linked cardiac hypertrophy

Abstract: Lo CW. A novel mouse model of X-linked cardiac hypertrophy. Am J Physiol Heart Circ Physiol 294: H2701-H2711, 2008. First published April 18, 2008 doi:10.1152/ajpheart.00160.2007.-We recovered a novel mouse mutant exhibiting neonatal lethality associated with severe fetal cardiac hypertrophy and with some adult mice dying suddenly with left ventricular hypertrophic cardiomyopathy. Using Doppler echocardiography, we screened surviving adult mice in this mutant line for cardiac hypertrophy. Cardiac dimensions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…Based on previous reports and the findings of this study we believe that VLCAD deficiency in mice results in CM starting with histological abnormalities (Exil et al 2003) that progress into structural changes, as observed in this study, and eventually into functional changes (Leatherbury et al 2008;Shen et al 2009;Yang et al 1999). Aerobic interval training was well tolerated by VLCAD-/-deficient mice that survived the training, although it appears to cause little or no adaptations in either heart function or heart structure.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Based on previous reports and the findings of this study we believe that VLCAD deficiency in mice results in CM starting with histological abnormalities (Exil et al 2003) that progress into structural changes, as observed in this study, and eventually into functional changes (Leatherbury et al 2008;Shen et al 2009;Yang et al 1999). Aerobic interval training was well tolerated by VLCAD-/-deficient mice that survived the training, although it appears to cause little or no adaptations in either heart function or heart structure.…”
Section: Resultssupporting
confidence: 83%
“…Similar to this study they reported normal %FS values (&50%) for all three genotypes. In contrast to the aforementioned findings, the %FS was previously shown to be significantly depressed in mice with left ventricular hypertrophic cardiomyopathy (Leatherbury et al 2008;Shen et al 2009) and dilated cardiomyopathy (Lee et al 2004) using cardiac measurements from M-mode images. In contrast to the results reported by Exil et al (2003), this study demonstrated that VLCAD-/-had significantly larger LV wall thicknesses and significantly smaller chamber dimensions (see Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Thus with the ultrasound biomicroscope, it is possible to quantitatively assess blood flow velocity and obtain other measurements of cardiovascular function using M-mode echocardiogram, color-flow Doppler imaging and pulsed-wave Doppler for blood flow velocity mapping, tissue Doppler imaging, and speckle tracking measurements (Leatherbury et al, 2003;Shen et al, 2005;Momoi et al, 2008;Yu et al, 2008). With speckle tracking, it is possible to quantitatively assess regional myocardial wall motion and obtain measurements of ventricular mechanics (Hu and Clark, 1989;Keller et al, 1996;Tobita and Keller, 1999;Tobita and Keller, 2000;Ishiwata et al, 2003;Leatherbury et al, 2008;Watanabe et al, 2009;Frank et al, 2010).…”
Section: High-resolution Ultrasound Biomicroscopymentioning
confidence: 99%
“…EKV imaging provides a higher temporal resolution than B-mode so cardiac wall abnormalities can be assessed. For EKV imaging, the transducer was attached to a fixed arm, and, over 6 min, synchronized electrocardiogram (ECG) signals and B-mode images were acquired and then processed for reconstruction of two-dimensional cine spanning one cardiac cycle (12,15).…”
Section: Methodsmentioning
confidence: 99%